Catheter Ablation vs. Anti-Arrhythmic Drugs as First-Line Treatment in Symptomatic Paroxysmal Atrial Fibrillation: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Saglietto, Andrea; Gaita, Fiorenzo; De Ponti, Roberto; De Ferrari, Gaetano Maria; Anselmino, Matteo (Frontiers in Cardiovascular Medicine, 2021)
Background: Catheter ablation has become a well-established indication for long-term rhythm control in atrial fibrillation (AF) patients refractory to anti-arrhythmic drugs (AADs). Efficacy and safety of atrial fibrillation catheter ablation (AFCA) before AADs failure are, instead, questioned. Objective: Aim of the study was to perform a systematic review and meta-analysis of randomized controlled trials (RCTs) comparing first-line AFCA vs AADs in symptomatic patients with paroxysmal AF. Methods: We performed random effect meta-analysis of binary outcome events comparing AFCA vs AADs in rhythm control naïve patients. The primary outcomes, also stratified by the type of ablation energy (radiofrequency or cryoenergy), were (1) recurrence of atrial tachyarrhythmias and (2) recurrence of symptomatic atrial tachyarrhythmias. Secondary outcomes included adverse events. Results: Six RCTs were included in the analysis. AFCA was associated with lower recurrences of atrial tachyarrhythmias (RR 0.58 [0.46-0.72]), consistent across the two types of ablation energy (radiofrequency: RR 0.50 [0.28-0.89]; cryoenergy: RR 0.60 [0.50-0.72]; p-value for subgroup differences: 0.55). Similarly, AFCA was related to less symptomatic arrhythmic recurrences (RR 0.46 [0.27-0.79]). Overall, adverse events did not differ. A trend towards increased periprocedural cardiac tamponade or phrenic nerve palsy was observed in the AFCA group, while more atrial flutter episodes with 1:1 atrioventricular conduction and syncopal events were reported in the AADs group. Conclusions: First-line rhythm control therapy with AFCA, independent from the adopted energy source (radiofrequency or cryoenergy), reduces long-term arrhythmic recurrences in patients with symptomatic paroxysmal AF compared to AADs.